Carbon Emission Evaluation and Low Carbon Economy Optimization Scheduling of Rural Integrated Energy System Based on LCA Method - Chunxiao Wu (IEEE Access)
Rural energy has the characteristics of diversity, dispersion, and regionalism. The construction and operation of its comprehensive energy system are essential for promoting the development of a low-carbon economy in rural areas and reducing carbon emissions. In response, the structure of the rural integrated energy system is initially analyzed and the equipment is planned. Subsequently, the carbon emission in each link of the power generation system is estimated by using the life cycle assessment method. Based on the evaluation results, a suitable low-carbon economy optimal scheduling model is established. The generator set and energy storage equipment in the integrated energy system are designed to enhance the efficiency of energy utilization. Then, the life cycle assessment method is used to calculate the carbon emissions of each stage. Next, the optimal scheduling model is established by taking the minimum carbon emissions and system operating costs as the objective function. In addition, the study introduced a water method and a kinetic accelerator to capture carbon dioxide and feed it into a high-pressure pump for storage. This will enable carbon capture and net zero emissions. The findings revealed that Model 1 exhibited minimal carbon emissions, amounting to 48,530.5 kg, and a comparatively low total operating cost of 30,625.48. After being applied to practical systems, the carbon emissions have been significantly reduced. The research model can effectively guide the low-carbon transformation of rural integrated energy systems and provide important technical support for achieving sustainable development goals in rural areas.